Immortalized Parkinson's disease lymphocytes have enhanced mitochondrial respiratory activity - Sarah J. Annesley; Sui T. Lay; Shawn W. De Piazza; Oana Sanislav; Eleanor Hammersley; Claire Y. Allan; Lisa M. Francione; Minh Q. Bui; Zhi-Ping Chen; Kevin R. W. Ngoei; Flora Tassone; Bruce E. Kemp; et al. (The Company of Biologists, 2016)
In combination with studies of post-mortem Parkinson's disease (PD) brains, pharmacological and genetic models of PD have suggested that two fundamental interacting cellular processes are impaired - proteostasis and mitochondrial respiration. We have re-examined the role of mitochondrial dysfunction in lymphoblasts isolated from individuals with idiopathic PD and an age-matched control group. As previously reported for various PD cell types, the production of reactive oxygen species (ROS) by PD lymphoblasts was significantly elevated. However, this was not due to an impairment of mitochondrial respiration, as is often assumed. Instead, basal mitochondrial respiration and ATP synthesis are dramatically elevated in PD lymphoblasts. The mitochondrial mass, genome copy number and membrane potential were unaltered, but the expression of indicative respiratory complex proteins was also elevated. This explains the increased oxygen consumption rates by each of the respiratory complexes in experimentally uncoupled mitochondria of iPD cells. However, it was not attributable to increased activity of the stress- and energy-sensing protein kinase AMPK, a regulator of mitochondrial biogenesis and activity. The respiratory differences between iPD and control cells were sufficiently dramatic as to provide a potentially sensitive and reliable biomarker of the disease state, unaffected by disease duration (time since diagnosis) or clinical severity. Lymphoblasts from control and PD individuals thus occupy two distinct, quasi-stable steady states; a 'normal' and a 'hyperactive' state characterized by two different metabolic rates. The apparent stability of the 'hyperactive' state in patient-derived lymphoblasts in the face of patient ageing, ongoing disease and mounting disease severity suggests an early, permanent switch to an alternative metabolic steady state. With its associated, elevated ROS production, the 'hyperactive' state might not cause pathology to cells that are rapidly turned over, but brain cells might accumulate long-term damage leading ultimately to neurodegeneration and the loss of mitochondrial function observed post-mortem. Whether the 'hyperactive' state in lymphoblasts is a biomarker specifically of PD or more generally of neurodegenerative disease remains to be determined.